Serum levels of cardiac troponin-T in adult patients with epilepsy - Makwela, Dimakatso Sethepele Ansion (My University, 2020)
BACKROUND: Myocardial infarctions have been reported in association with seizures. In older age groups, an elevated risk of myocardial injury exists through the presence of vascular risk factors such as hypertension, diabetes and dyslipidemia. Elevated cardiac specific troponins in an epileptic patient suggest the probability of cardiac ischemia AIMS: Firstly, to compare cardiac troponin-T (cTnT) levels in patients with different causes and severity of epilepsy, within seven days of having had a seizure. Secondly, to assess if elevated cTnT levels in patients with epilepsy are associated with the presence of cardiovascular risk factors. METHODS: This prospective study included 122 adult epilepsy patients, recruited over a period of approximately 7 months, who presented within 7 days of having had a seizure at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH), Chris Hani Baragwanath Academic Hospital (CHBAH) and Helen Joseph Hospital (HJH). The patients were noted to have presented with either status epilepticus, stable or unstable epilepsy. RESULTS: The mean age was 43.6 years with a range of 18 to 85 years. Cardiac troponin-T levels were elevated in 24(19.6%) patients, 15 of whom had presented in status epilepticus. Twenty-six subjects were over 60 years in age. In this older age group, 17 (65.3%) had elevated cTnT levels. Of a total of 26 hypertensive patients, 13 (50.0%) had elevated cTnT, moreover, of 11 diabetic patients, 7 (63.6%) were also found to have elevated cTnT levels. CONCLUSION: Troponin-T levels were found to be elevated in patients with epilepsy. This sensitive marker of cardiac tissue injury being elevated adds some support to the notion that myocardial injury can occur as a complication of seizures. Patients with complicated epilepsy, such as status epilepticus, the elderly and patients with vascular risk factors, are at particular risk for myocardial injury when they have seizures.
A research report submitted in partial fulfilment for the degree of Master of Medicine in the division of Neurology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019